2018
DOI: 10.1002/ptr.6219
|View full text |Cite
|
Sign up to set email alerts
|

(+)‐Isobicyclogermacrenal and spathulenol from Aristolochia yunnanensis alleviate cardiac fibrosis by inhibiting transforming growth factor β/small mother against decapentaplegic signaling pathway

Abstract: Cardiac fibrosis contributes to both systolic and diastolic dysfunction in many cardiac pathophysiologic conditions. Antifibrotic therapies are likely to be a crucial strategy in curbing many fibrosis‐related cardiac diseases. In our previous study, an ethyl acetate extract of a traditional Chinese medicine Aristolochia yunnanensis Franch. was found to have a therapeutic effect on myocardial fibrosis in vitro and in vivo. However, the exact chemicals and their mechanisms responsible for the activity of the cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Spathulenol 1Immunomodulator [32], anti-nociceptive [64], antimicrobial [65], alleviates cardiac fibrosis [66], antioxidant [33], antiproliferative, antimycobacterial [33], anti-inflammatory [33,67], antitumor [67].…”
Section: Secondary Metabolite Biological Activitiesmentioning
confidence: 99%
“…Spathulenol 1Immunomodulator [32], anti-nociceptive [64], antimicrobial [65], alleviates cardiac fibrosis [66], antioxidant [33], antiproliferative, antimycobacterial [33], anti-inflammatory [33,67], antitumor [67].…”
Section: Secondary Metabolite Biological Activitiesmentioning
confidence: 99%
“…Complications of intensive chemotherapeutic treatment for a patient suffering from leukemia include risk of death from cardiac and neurological complications [ 4 ], oral mucositis [ 5 ], gastrointestinal and liver toxicities [ 6 ], an infectious complication for ALL patients [ 7 ] and reduced bone mineral density at a high rate for children with ALL [ 8 , 9 ]. In spite of causing several side effects, the overuse of these drugs leads to chemotherapeutic drug resistance in leukemia cells [ 10 ]. Thus, the production of new therapeutic drugs having higher potency and lower toxicity is important to expanding the overall life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Sesquiterpenoids from the TCM A. yunnanensis were previously reported to possess certain anticardiac fibrosis effects on TGFβ1-stimulated cardiac fibroblasts . However, the potential target, the SARs, and the in vivo efficacy of these compounds are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent chemical investigation led to the isolation of a group of sesquiterpenoids . These sesquiterpenoids exhibited certain anticardiac fibrosis effects on TGFβ1-stimulated cardiac fibroblasts, and the mechanistic study revealed their inhibition on the TGFβ/Smad signaling pathway . However, the potential target, the structure–activity relationships (SARs), and the in vivo efficacy of these compounds are still unclear.…”
Section: Introductionmentioning
confidence: 99%